Analysis of SIW Crossover for 5G Beamforming Network Applications - Matar, Mohammed A. I.; Cinar, Gokhan; Ã‡Ä±nar, Ã–zge (International Journal of Engineering and Technology, 2022)
A Mode-Matching Technique (MMT) with Generalized Scattering Matrix Method (GSMM) are deployed to design and analyze H-plane SIW crossover operating at 26 GHz for 5G beamforming networks applications. The introduced crossover has an 0 dB transmission over more than 4 GHz bandwidth. During the MMT formulation, the crossover structure is divided into two symmetrical cascaded parts with each part having multi-port bifurcated sections. Due to the symmetrical structure, analyzing one half of the coupler with MMT has been sufficient for full analysis. The obtained S-parameter results from MMT are compared with full-wave CST simulator results.